2016
DOI: 10.1002/iub.1502
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNA 126 in screening, diagnosis, and prognosis of diabetic patients in Egypt

Abstract: MicroRNAs (miRNAs), family of non-coding small RNAs, play a vital role in the regulation of blood glucose level. We aimed to investigate the relation of serum miRNA-126 expression with impaired glucose tolerance as well as type 2 diabetes mellitus (T2DM) patients with and without complications. One hundred healthy controls, eighty-six patients with IGT, and one hundred patients with T2DM were recruited in this study. Serum miRNA-126 expression was assessed by quantitative real-time polymerase chain reaction. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 25 publications
3
43
1
Order By: Relevance
“…The finding of PDR‐specific miRNAs in our study was consistent with other studies (as shown in Table ). Recently, miR‐150‐5p was found to be strongly down‐regulated in the extracellular vesicles of blood from DR subjects using miRNA array detection and suppression of the pathological neovascularization in mice using oxygen‐induced proliferative retinopathy .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding of PDR‐specific miRNAs in our study was consistent with other studies (as shown in Table ). Recently, miR‐150‐5p was found to be strongly down‐regulated in the extracellular vesicles of blood from DR subjects using miRNA array detection and suppression of the pathological neovascularization in mice using oxygen‐induced proliferative retinopathy .…”
Section: Discussionsupporting
confidence: 93%
“…25 In our previous study, we also used NGS to explore the miRNA profile in the AH of glaucoma patients, and we found glaucoma specific miRNAs profile and related to glaucoma progression. 19 The finding of PDR-specific miRNAs in our study was consistent with other studies [26][27][28] (as shown in Table 3). Recently, miR-150-5p was found to be strongly downregulated in the extracellular vesicles of blood from DR subjects using miRNA array detection 13 and suppression of the pathological neovascularization in mice using oxygeninduced proliferative retinopathy.…”
Section: Discussionsupporting
confidence: 92%
“…Circulating miR-126 level has been negatively correlated with fasting blood glucose and hemoglobin A1c [27]. Interestingly, in contrast to blood miR-126, our meta-analyses showed that urinary miR-126 excretion was significantly increased in patients with DN, although there was a significant heterogeneity.…”
Section: Discussionmentioning
confidence: 57%
“…The main characteristics extracted from various datasets are summarized in Table 1, which includes the number of patients investigated, the measurement platform, type of sample used and the identity of miRNAs in the study [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Comparing results from multiple tissues provides an overall view of the impact of miRNAs in T2DM pathology.…”
Section: Resultsmentioning
confidence: 99%